Kerjasama United Nations International Children Fund’s (UNICEF) Dalam Mengatasi Child Sexual Abuse di Indonesia Tahun 2017-2019 - Adhanofa, Alfadhea Ajeng Avishanic Zasha; Fretes, Christian Herman Johan de; Simanjuntak, Triesanto Romulo (Jurnal Social Science, 2024)
UNICEF plays an important role in combating sexual violence against children in Indonesia, with the number of victims increasing from 190 in 2018 to 419 in 2020. UNICEF's role is based on institutional liberalism, which suggests that the organization functions as a medium of information and negotiation opportunity. The organization collects, analyzes, shares, disseminates, and provides information from its point of view or opinion, taking into account personal and family background information and the social environment. UNICEF is working with other organizations to collect basic data on sexual violence against children in Indonesia. UNICEF has helped Indonesia develop legislation to protect children's rights, such as the Child Protection Law of 2002, which aims to address the long-term negative impacts of sexual violence on children's physical and mental health. The Birth Certificate for All program has an impact on data collection and implementation of the Child Protection Law, which can be used as public information and further develop the prevention of sexual violence against children in Indonesia.